Memoirs of the Life and Correspondence of Henry Reeve, C.B., D.C.L. : In Two Volumes. Volume II. - Reeve, Henry, 1813-1895; Laughton, John Knox, 1830-1915 (Salt Lake City, UT : Project Gutenberg, 2006)
"Memoirs of the Life and Correspondence of Henry Reeve, C.B., D.C.L." by John Knox Laughton is a historical account likely written in the late 19th century. This work provides an intriguing glimpse into the life of Henry Reeve, capturing his extensive correspondence and reflections, particularly set against the backdrop of significant historical events such as the wars in Italy during the 1850s and the political dynamics of that era. At the start of the memoirs, the reader is introduced to discussions surrounding the political relations of France and Italy, particularly through the lens of the Italian War of Independence. The narrative details the build-up to conflict, highlighting secret negotiations, military mobilizations, and the tensions leading to the war. It captures Reeve's correspondence regarding the hopes and anxieties of the time, interspersed with personal updates about friends and acquaintances, showcasing his active engagement in the political discourse of his day. This opening sets the stage for a deeper understanding of Reeve's life, his connections with influential figures, and the turbulent historical context in which he lived. (This is an automatically generated summary.)
Release date is 2006-02-01
Produced by Charles Franks, Keren Vergon, Charles Aldarondo and PG Distributed Proofreaders
Keywords: Reeve, Henry, 1813-1895; Reeve, Henry, 1813-1895 -- Correspondence; Journalists -- Great Britain -- 19th century -- Biography